2015
DOI: 10.1016/j.ajic.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Health care–associated infection outbreaks in pediatric long-term care facilities

Abstract: Children in pediatric long-term care facilities (pLTCFs) have complex medical conditions and increased risk for health care-associated infections (HAIs). We performed a retrospective study from January 2010-December 2013 at 3 pLTCFs to describe HAI outbreaks and associated infection control interventions. There were 62 outbreaks involving 700 cases in residents and 250 cases in staff. The most common interventions were isolation precautions and education and in-services. Further research should examine interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For this study, outbreaks of acute respiratory infections were defined as ≥ 2 cases of the same laboratory-confirmed pathogen or ≥ 2 cases on the same unit with the same symptoms. 32…”
Section: Rates Of Infections and Hospitalizations-ongoing Medical Recmentioning
confidence: 99%
“…For this study, outbreaks of acute respiratory infections were defined as ≥ 2 cases of the same laboratory-confirmed pathogen or ≥ 2 cases on the same unit with the same symptoms. 32…”
Section: Rates Of Infections and Hospitalizations-ongoing Medical Recmentioning
confidence: 99%
“…3 Cases were considered part of an outbreak if they occurred within the maximum incubation period of the pathogen defined by Red Book. 5 …”
Section: Data Collectionmentioning
confidence: 99%
“…Several outbreaks, particularly of viral upper respiratory infections, have been reported in pLTCFs across the country (James et al, 2007; Kopel et al, 2010). Between January 2010 and December 2013 in the three pLTCFs included in this current study, we identified 62 outbreaks involving 700 cases in residents and 250 cases in staff (Murray et al, 2015). Furthermore, we conducted a survey at the 2013 Pediatric Complex Care Association Annual National Conference in which pLTCF providers reported infection prevention and control issues of greatest concern in a survey, including the lack of best practice guidelines, multidrug-resistant bacteria, and viral respiratory infections (Murray et al, 2014).…”
mentioning
confidence: 99%